Equation of state of sticky-hard-sphere fluids in the chemical-potential route - Rohrmann, Rene Daniel (2014)
The coupling-parameter method, whereby an extra particle is progressively coupled to the rest of the particles, is applied to the sticky-hard-sphere fluid to obtain its equation of state in the so-called chemical-potential route (μ route). As a consistency test, the results for one-dimensional sticky particles are shown to be exact. Results corresponding to the three-dimensional case (Baxter's model) are derived within the Percus-Yevick approximation by using different prescriptions for the dependence of the interaction potential of the extra particle on the coupling parameter. The critical point and the coexistence curve of the gas-liquid phase transition are obtained in the μ route and compared with predictions from other thermodynamics routes and from computer simulations. The results show that the μ route yields a general better description than the virial, energy, compressibility, and zero-separation routes.